FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN AUDITOR MENERIMA PENUGASAN PADA KANTOR AKUNTAN PUBLIK DI SUMATERA BAGIAN SELATAN - Andre Leonardo R; Rochmawati Daud (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
This research intends to find out the factors that influence auditor 's judgment in client acceptance decision. Analysis unit in this research is public accountant/ auditor. To resolve this problem, the applied regression technique is analysis of multiple linear regression models by means of aiuiliary software of SPSS 11,0 version. This research proved that audit risk, audit fee , independency and integrity of management simultaneously influenced the auditor 's judgment in client acceptance decision. However from partially test that has been done, proved that audit risk, idependency and integrity of management influenced the auditor's judgment in clietii acceptance decision, whereas the audit fee factor did not influenced the auditor's judgment in client acceptance decision. And integrity of management is the most dominant factor for aitditor's judgment in client acceptance decision. Key words: Auditor fudgment in client acceptance decision, audit risk, independency, audit fee, integrity of management